Yield of Fodder Maize (Zea mays) and its Chemical Composition under Varying Plant Densities and Nutrient Management - Subrahmanya, D. J.; Kumar, Rakesh; Tyagi, Nitin; Ram, Hardev; Singh, Magan; Meena, R. K.; Tamta, A.; Pandey, A. K. (Indian Journal of Animal Nutrition, 2017)
An experiment consisting of four plant densities (45, 60, 75 and 90 kg/ha seed rate) and five fertilizer levels (0, 50, 75, 100 and 125% recommended dose of fertilizers; RDF) was laid out in split plot design to find out the yield and chemical composition of fodder maize (Zea mays L.). Application of 60 kg/ha seed rate increased(P